2021
DOI: 10.2991/ahsr.k.211105.021
|View full text |Cite
|
Sign up to set email alerts
|

The Episiotomy Effect of Topical Combination of Cinnamon Oil and Red Betel on Skin Wound Healing Mechanism

Abstract: The process of episiotomy surgery during childbirth results in injury and pain in the perineum. This study aims to evaluate the effect of the topical combination of cinnamon oil and red betel extract on the healing process of episiotomy incision model in Swiss mice. The research subjects were divided into six groups: (I) Negative control, (II) positive control, (III) mice treated with cinnamon oil, (IV) mice treated with red betel extract, (V) mice treated with 2 ml cinnamon oil and 20% red betel extract, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…In this study it was found that giving red betel leaf ointment was effective in accelerating the healing of perineal wounds degrees 1, 2 and 3 in postpartum mothers less than 7 days after the puerperium and can decrease the possibility of infection. This study is in accordance with several previous studies which stated that red betel leaf compounds were effective in accelerating the healing of perineal wounds after childbirth (Alfiana et al, 2022;Damarini et al, 2013b;Emelda et al, 2021;Kyu et al, 2018;Stianto et al, 2018). It's just that most previous studies used boiled water from red betel leaves and had not yet formed an ointment with a measurable dose for how to use it.…”
Section: Discussionsupporting
confidence: 93%
“…In this study it was found that giving red betel leaf ointment was effective in accelerating the healing of perineal wounds degrees 1, 2 and 3 in postpartum mothers less than 7 days after the puerperium and can decrease the possibility of infection. This study is in accordance with several previous studies which stated that red betel leaf compounds were effective in accelerating the healing of perineal wounds after childbirth (Alfiana et al, 2022;Damarini et al, 2013b;Emelda et al, 2021;Kyu et al, 2018;Stianto et al, 2018). It's just that most previous studies used boiled water from red betel leaves and had not yet formed an ointment with a measurable dose for how to use it.…”
Section: Discussionsupporting
confidence: 93%